Literasi dan Ujaran Kebencian Dalam Balutan Liberalisme Media Sosial - Edison Bonar Tua Hutapea; Faisyal .; Kresna Edy Santoso (Oratio Directa (Prodi Ilmu Komunikasi), 2022)
Abstraction Liberalism gives individual freedom to move, based on this understanding, some people carry out activities that violate the law, such as hate speech, insults, curses and spreading hoaxes on social media. Now there are so many politically motivated hoaxes being spread by power hunters. They construct wrong assumptions in people's heads. Long before there was a modern state, and hate speech social media existed. Hate speech occurred between tribes, causing wars between tribes. To reduce the negative impact, it is necessary to increase public understanding of mass media, including understanding of social media, which is called media literacy and digital literacy. Keywords: Liberalism, Social Media, Hate Speech, Media Lietration